Circumcision Social Service for Poor Families in Andepali Village, Sampara District: Bakti Sosial Khitanan Pada Keluarga Tidak Mampu Di Desa Andepali Kecamatan Sampara - La Ode Alifariki; La Rangki; Adius Kusnan (Yayasan Ahmar Cendekia Indonesia, 2022)
Circumcision is the act of cutting or removing part or all of the skin covering the front of the penis. Circumcision is very beneficial for health, namely reducing the risk of urinary tract infections, overcoming phimosis, paraphimosis, balaniditis and can reduce the risk of penile malignancy and the spread of sexually transmitted diseases. This method of service is carried out by promoting community service activities in Andepali, then for those who are interested register to the committee. The committee will screen the participants for mass circumcision according to indications. The implementation of the activities will be carried out according to a specified schedule involving the health team from the Faculty of Medicine, Halu Oleo University and the Puskesmas. The result of this community service is that a mass circumcision has been carried out at the Andepali Village Meeting Hall, Sampara sub-district on March 6, 2019, which was attended by 25 patients who underwent circumcision. There are 6 health workers in the service team consisting of general practitioners, nurses and students of the Faculty of Medicine, Halu Oleo University. The conclusion of this community service has been circumcision and mass treatment of economically disadvantaged patients. Abstrak Khitan merupakan tindakan memotong atau menghilangkan sebagian atau seluruh kulit penutup depan dari penis. Khitan sangat bermanfaat untuk kesehatan yaitu mengurangi resiko infeksi saluran kencing, mengatasi fimosis, parafimosis, balaniditis dan dapat mengurangi resiko keganasan penis serta penyebaran penyakit menular seksual. Metode pengabdian ini di laksanakan dengan promosi kegiatan pengabdian kepada masyarakat Andepali, kemudian bagi yang berminat mendaftar ke panitia. Panitia akan melakukan screening untuk peserta khitan massal yang sesuai indikasi. Pelaksanaan kegiatan akan dilaksanakan sesuai jadwal yang ditentukan yang melibatkan tim kesehatan dari Fakultas Kedokteran Universitas Halu Oleo dan Pihak Puskesmas. Hasil pengabdian masyarakat ini berupa telah dilaksanakan khitan massal di Balai Pertemuan Desa Andepali, kecamatan Sampara pada tanggal 6 Maret 2019 yang diikuti oleh peserta yang menjalani khitan sebanyak 25 pasien. Petugas kesehatan sebanyak 6 tim pengabdi terdiri atas dokter umum, perawat dan mahasiswa Fakultas Kedokteran Universitas Halu Oleo. Kesimpulan pengabdian masyarakat ini telah di lakukan khitan dan pengobatan massal terhadap pasien tidak mampu secara ekonomi.